Reduction of metal adducts in oligonucleotide mass spectra in ion‐pair reversed‐phase chromatography/mass spectrometry analysis. (22nd June 2016) - Birdsall, Robert E.; Gilar, Martin; Shion, Henry; Yu, Ying Qing; Chen, Weibin
Abstract : Rationale: Electrospray ionization mass spectrometry (ESI‐MS)‐based techniques commonly used in oligonucleotide analyses are known to be sensitive to alkali metal adduct formation. Adducts directly impact the sensitivity of MS‐based analyses as the available charge is distributed across the parent peak and adduct(s). The current study systematically evaluated common liquid chromatography (LC) components in LC/ESI‐MS configurations used in oligonucleotide analysis to identify metal adduct contributions from LC instrumentation. Methods: A UPLC liquid chromatography system was configured with a single quadrupole MS detector (ACQUITY QDa, Waters Corp.) to monitor adduct formation in oligonucleotide separations. An ion‐pairing mobile phase comprised of 15 mM triethylamine and 400 mM hexafluoro‐2‐propanol was used in conjunction with an oligonucleotide separation column (Waters OST BEH C18, 2.1 mm × 50 mm) for all separations. A 10‐min method was used to provide statistical figures of merit and evaluate adduct formation over time. Results: Trace alkali metal salts in the mobile phase and reagents were determined to be the main source of metal salt adducts in LC/ESI‐MS‐based configurations. Non‐specific adsorption sites located throughout the fluidic path contribute to adduct formation in oligonucleotide analyses. Ion‐pairing mobile phases prepared at neutral or slightly basic pH result in up to a 57% loss of spectral abundance to adduct formation in the current study. Conclusions: Implementation of a short low pH reconditioning step was observed to effectively displace trace metal salts non‐specifically adsorbed to surfaces in the fluidic path and was able to maintain an average MS spectral abundance ≥94% with a high degree of repeatability (relative standard deviation (R.S.D.) 0.8%) over an extended time study. The proposed method offers the ability to rapidly regenerate adsorption sites with minimal impact on productivity while retaining assay sensitivity afforded by MS detection with reduced adduct formation. © 2016 The Authors. Rapid Communications in Mass Spectrometry Published by John Wiley & Sons Ltd.